218k views
2 votes
Consider f(x)=x+7 and g(x)=x^2-1 find (g of f)(x)

User Dlsa
by
5.3k points

2 Answers

3 votes

(g o f) (x) = g ( f(x) )

= (x+7)² – 1

= x² + 14x+49 – 1

= x² + 14x+48

If you want, (f o g ) (x) below is the solution ^_^

(f o g ) (x) = f ( g(x) )

= g(x) + 7

= x²-1 +7

= x² +6

I hope I helped you^_^

User Gscaparrotti
by
5.9k points
2 votes

Answer:

g(f(x))=x^2 + 14x + 48

Explanation:

you insert (x+7) into every x in the g(x) equation, so g(x)=(x+7)^2 - 1. then you simplify it by doing (x+7)(x+7) which gets you x^2 + 14x + 49. then you subtract the 1 from the equation to get g(f(x))=x^2 + 14x + 48.

User Jagoly
by
5.5k points